Meniscal Repair with Concurrent Anterior Cruciate Ligament Reconstruction: Is ACL Graft Choice Predictive of Meniscal Repair Success?. Issue 7 (29th July 2019) - Salem, Hytham S.; Huston, Laura J.; Zajichek, Alex; Wolcott, Michelle Lora; McCarty, Eric C.; Vidal, Armando F.; Bravman, Jonathan T.; Group, MOON Knee; Spindler, Kurt P.; Frank, Rachel M.
Objectives: The success rate of meniscal repair is known to increase with concurrent anterior cruciate ligament (ACL) reconstruction. However, the influence of ACL graft choice has not been described. The current study examines the effect of ACL graft choice on the outcome of meniscal repair performed in conjunction with ACL reconstruction (ACLR). Methods: Patients who underwent meniscal repair with concurrent primary ACLR were identified from a longitudinal, prospective cohort. Patient demographics and subjective outcome measures including the International Knee Documentation Committee (IKDC), Knee injury and Osteoarthritis Outcome Score (KOOS), and Marx activity rating scale were collected preoperatively. Arthroscopic assessment of meniscal tear characteristics and associated repair technique were recorded intraoperatively. Patients with subsequent repair failure, defined as any subsequent surgical procedure addressing the meniscus repaired at index surgery, were identified and operative notes were obtained in order to accurately classify pathology and treatment. A logistic regression model was built to assess the association of patient specific factors, ACL graft, baseline Marx activity level and meniscal tear laterality with the occurrence of repair failure at 6-year follow-up. Results: A total of 646 patients underwent ACLR with concurrent meniscal repair. Bone-patellar tendon-bone (BTB) and soft tissue (ST) autograft were used in 55.7% and 33.9% of cases, respectively, while allografts were utilized in the remaining cases. Table 1 summarizes the univariate analysis of each baseline variable. A total of 101 patients (15.6%) required subsequent surgery on the meniscus repaired at index surgery, including 89 meniscectomies (87 partial, 2 subtotal), 11 revision meniscal repairs, and 1 meniscus allograft transplantation. No statistically significant difference in meniscal repair failure rate was observed based on patient age, sex, BMI or smoking status. The odds of meniscal repair failure within 6 years of surgery for patients with only a lateral meniscal repair are 68% less than those with only a medial meniscal repair (CI: 41%, 83%; p<0.001). There is a statistically significant relationship between baseline Marx activity and the risk of subsequent meniscal repair, though it is nonlinear—patients with low or high baseline activity are at the highest risk of meniscal repair failure (CI: 1.05, 1.31; p=0.004, Figure 1). The estimated odds of meniscal repair failure for BTB allograft, ST allograft, and ST autograft were 2.78 (CI: 0.84, 9.19; p=0.09), 2.29 (CI: 0.97, 5.45; p=0.06), and 1.42 (CI:0.87, 2.32; p=0.16) times that of BTB autograft, respectively, although none proved statistically significant. Meniscal repair failure is associated with significantly lower 6-year scores for all KOOS components and the IKDC (p<0.001). However, there was no significant difference in MARX activity at 6-years (p=0.27). Conclusion: In the setting of primary ACLR, the risk of meniscal repair failure is increased with medial versus lateral meniscal repair. Patients with low or high baseline activity levels are also at an increased risk. ACL graft choice seems to have an effect on meniscal repair failure that approaches but does not reach statistical significance. A larger sample size may be required to accept the null hypothesis. Table 1. Univariate summary of each baseline characteristic Variable Level Summary Age (years) 20.00 (16.00, 28.00) Sex Female 281 (43.50%) Male 365 (56.50%) BMI 24.40 (22.0, 27.40) NA 11 (1.70%) Smoking Status Current 64 (9.91%) Never 524 (81.11%) Quit 46 (7.12%) NA 12 (1.86%) Baseline Marx Activity 14.00 (9.00, 16.00) NA 4 (0.62%) ACL graft type Allograft (BTB) 22 (3.41%) Autograft (BTB) 360 (55.73%) Allograft (Soft tissue) 45 (6.97%) Autograft (Soft tissue) 219 (33.90%) Meniscal repair location Both 39 (6.04%) Lateral 187 (28.95%) Medial 420 (65.02%) Vaues reported as median (IQR) for numeric values and counts (%) for categorical variables BMI, Body mass index; BTB, Bone-patellar tendon-bone; NA, Not available Figure 1. Profile plot of the relationship between baseline MARX activity and the risk of subsequent meniscal repair